Damaging intermolecular energy and proton transfer processes in alpha-particle-irradiated hydrogen-bonded systems - Xu, Shenyue; Dorn, Alexander; Cederbaum, Lorenz S.; Kryzhevoi, Nikolai V. (Angewandte Chemie. International edition, 2018)
Although the biological hazard of alpha-particle radiation is well-recognized, the molecular mechanisms of biodamage are still far from being understood. Irreparable lesions in biomolecules may not only have mechanical origin but also appear due to various electronic and nuclear relaxation processes of ionized states produced by an alpha-particle impact. Two such processes were identified in the present study by considering an acetylene dimer, a biologically relevant system possessing an intermolecular hydrogen bond. The first process is the already well-established intermolecular Coulombic decay of inner-valence-ionized states. The other is a novel relaxation mechanism of dicationic states involving intermolecular proton transfer. Both processes are very fast and trigger Coulomb explosion of the dimer due to creation of charge-separated states. These processes are general and predicted to occur also in alpha-particle-irradiated nucleobase pairs in DNA molecules.